2021
DOI: 10.1093/cid/ciab001
|View full text |Cite
|
Sign up to set email alerts
|

Emergence and Transmission of Daptomycin and Vancomycin-Resistant Enterococci Between Patients and Hospital Rooms

Abstract: Background Vancomycin-resistant enterococci (VRE) are a major cause of morbidity and mortality in immunocompromised patients. Tracking the dissemination of VRE strains is crucial to understand the dynamics of emergence and spread of VRE in the hospital setting. Methods Whole genome sequencing (WGS) and phylogenetic analyses were performed to identify dominant VRE strains and potential transmission networks between 35 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…The most frequent MLST type in our study was ST117 within clonal complex 17 that after 2010 spread in health care settings in Germany [ 39 ]. In our setting the knowledge of the sequence type, however, in most cases was not helpful to track the in-hospital spread of individual VRE isolates, and therefore did not aid in the identification of potential sources of VRE, as this has been described in a recent study using whole genome sequencing for typing of VRE isolates [ 40 ]. In the dialysis group ST117 (42.8%) was significantly (p = 0,045) less frequent compared to the frequencies of ST117 in the other risk groups, which was in the range of 57.7–75% of all VRE isolates.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent MLST type in our study was ST117 within clonal complex 17 that after 2010 spread in health care settings in Germany [ 39 ]. In our setting the knowledge of the sequence type, however, in most cases was not helpful to track the in-hospital spread of individual VRE isolates, and therefore did not aid in the identification of potential sources of VRE, as this has been described in a recent study using whole genome sequencing for typing of VRE isolates [ 40 ]. In the dialysis group ST117 (42.8%) was significantly (p = 0,045) less frequent compared to the frequencies of ST117 in the other risk groups, which was in the range of 57.7–75% of all VRE isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Transmission of daptomycin-resistant strains of VRE were studied in an American cancer centre to understand the potential spread between patients and their environment. It was found that there was horizontal transfer of genetically related strains of VRE between patients on different floors of the hospital and within their room environment [13]. Future research is required to understand the influence of outlet design on the spread of pathogen contamination, and on the effectiveness of different disinfection and control approaches.…”
Section: Control and Interventionsmentioning
confidence: 99%
“…Common OPPPs include Legionella spp., nontuberculous mycobacteria and Pseudomonas aeruginosa [8]. These microorganisms form biofilms on the surface of pipes and water-related devices that can also provide refuge to pathogens not typically associated with drinking water including Staphylococcus aureus , Enterobacteriaceae, Klebsiella pneumoniae and Escherichia coli [9–14 ▪ ]. Biofilms provide protection against unfavourable environmental conditions including disinfection processes and deliver the ideal environment for the transfer of antimicrobial resistance genetic elements [10 ▪ ,15].…”
Section: Introductionmentioning
confidence: 99%
“…Daptomycin (DAP) is a preferred treatment for serious VRE infections and has demonstrated rapid biofilm penetration using fluorescent visualization [ 11 , 12 , 13 ]. Unfortunately, DAP-nonsusceptible (DNS) and DAP-susceptible dose-dependent (SDD) phenotypes are quickly emerging [ 14 , 15 , 16 , 17 , 18 ]. Substitutions in LiaS and LiaR of the LiaFSR pathway, enhances DAP’s selection for resistance, rendering the isolate unresponsive to DAP monotherapy, regardless of dose exposure [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%